The Washington State Constitution - Utter, Robert F. (Robert French), 1930- (Oxford commentaries on the state constitutions of the United States., 2013)
The Washington State Constitution provides an outstanding constitutional and historical account of the state's governing charter. In addition to an overview of Washington's constitutional history that focuses on the document's 19th century populist roots, it provides an in-depth, section-by-section analysis of the entire constitution, detailing the many significant changes made since its initial drafting. This treatment, along with a table of cases, index, and bibliography, provides an unsurpassed reference guide for lawyers, judges, scholars, and members of the general public. The second edit.